Medical Staff Shortages in Regional Healthcare: Challenges and Solutions - Aliyev, Shahmar; Ismayilzada, Zulfugar; Aliyev, Nijat (ADA University, 2025)
This capstone paper examines the long-lasting shortage and unequal distribution of medical staff in Azerbaijan’s regional healthcare system. The topic was chosen due to its critical impact on healthcare accessibility and effectiveness in the regions. The paper identified the root causes of staff shortages such as internal and external brain drain, educational disengagement, and over-centralized infrastructure. The paper proposes the most suitable, evidence-based policy solutions to address the existing problems. Methodologically, the research compares national healthcare statistics with international benchmarking standards through WHO and OECD, and qualitative insights from interviews with Azerbaijani healthcare professionals experienced in rural work. The mixed-methods approach ensured a deep understanding of both sides that contribute to the issue. The paper concludes by recommending a step-by-step implementation of a National Health Professional Retention and Diaspora Reintegration Program as the most effective solution, supported by educational pipeline reforms and mobile medical clinics to address short-term access gaps. These integrated measures aim to improve workforce retention, regional equity, and long-term system resilience.
Keywords: Medical personnel -- Supply and distribution.; Health services administration -- Regional disparities.; Health manpower policy -- Government policy.; Rural health services -- Personnel management.; Medical education -- Workforce development.